Analisis Harga Pokok Produksi Untuk Menentukan Harga Jual Produk Peci - Andri Ikhwana; Saepul (Institut Teknologi Garut, 2017)
This research was conducted in PD. Al-Iman, a business engaged in the production of peciand located in Kp. Ciranyang, Ds. Mekarjaya, Kec. Bayongbong Garut. This study aims to analyzehow the calculation of cost of production is applied. The calculation of the cost of production is usingthe full costing method and the costing variable of the difference between the two methods calculation,and for the determination of the selling price the method used in this research is the cost plus price(cost plus pricing method). The results showed that there are differences in the calculation of cost ofgoods sold and selling price based on the method of full costing and variable costing method.Calculation using full costing method resulted in higher selling price compared to variable costingmethod. So, should be in calculating the cost of production as the basis of determining the sellingprice using the full costing method, so that the resulting sale price is precise and accurate.